2021
DOI: 10.3390/agronomy11122429
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Synthetic Nitrogen Fertilizer with Different Types of Organic Materials Improves Grain Yield in China: A Meta-Analysis

Abstract: Synthetic nitrogen fertilizer substitution (NSS) with different types of organic material is a cleaner agricultural practice for reducing the application of synthetic N input in farmlands while also relieving the environmental issues caused by the discharge of organic wastes. However, the effects of the NSS practice on crop yields, being the primary objective of agricultural activity, is still uncertain in China. This study conducted a meta-analysis to assess the impacts of the NSS practices with different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This characteristic is beneficial to the nutrient supply and yield improvement of crops. Related studies have also shown the effect on production increase [39][40][41][42]. However, this study indicated that the contribution of organic materials to PC was small, although the total SOC s increased.…”
Section: Effects On Soc Stability Derived From Different Nss Practicesmentioning
confidence: 54%
“…This characteristic is beneficial to the nutrient supply and yield improvement of crops. Related studies have also shown the effect on production increase [39][40][41][42]. However, this study indicated that the contribution of organic materials to PC was small, although the total SOC s increased.…”
Section: Effects On Soc Stability Derived From Different Nss Practicesmentioning
confidence: 54%
“…Furthermore, the enhancement of SQ through the application of both organic and inorganic fertilizers has been validated as a means to secure sustainable crop yields (Ren et al, 2022). Substituting synthetic nitrogen fertilization has exhibited a notable capacity to elevate crop yields by 3.28%–7.68%, further corroborating a significant positive correlation between the crop yields and SQ (Fan et al, 2021). Implementation of reduced tillage methodologies has demonstrated a propensity to ameliorate soil's physical attributes, fostering conducive conditions for root development and optimal water movement, particularly in dense clay soils (Saglam et al, 2015).…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, the enhancement of SQ through the application of both organic and inorganic fertilizers has been validated as a means to secure sustainable crop yields (Ren et al, 2022). Substituting synthetic nitrogen fertilization has exhibited a notable capacity to elevate crop yields by 3.28%-7.68%, further corroborating a significant positive correlation between the crop yields and SQ (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 81%
“…Shifts in the concentration ratio of NH 4 + –N and NO 3 – –N content change the response of rice cultivars to soil available N, where cultivars with modified root features and highly responsive to soil N pools show increased N accumulation than the cultivars less responsive to soil N pools and with low NUE. Coupled organic and inorganic N fertilizer application can increase the rice grain yield but essentially requires the genotype selection process through integrated approaches of japonica and indica rice varieties ( Farooq et al, 2021 ) via integrative progressive crop management that can improve NUE and other crop features in physiological and agronomic perspectives ( Fan et al, 2021 ; Deng et al, 2022 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%